Alma Mahler - Monson, Karen; Sabalé, Hernán (Barcelona : Salvat editores, 1995)
La chica más guapa de Viena -- La viuda con nuevo genio -- Franz, poeta y revolucionario.
Keywords: Mahler, Alma -- (1879-1964) -- Biografía